Research on nonsteroidal anti-inflammatory drugs in Malaysia: a bibliometric analysis - Zin, Che Suraya; Nozid, Norzaini Ros; Razak, Amalia Athirah; Hashim, Siti Nuraisyah; Mazlan, Nur Aimi; Daud, Norhayati; Shaikh Rahman Bux, Siti Halimah Bux (Wolters Kluwer Medknow Publications, 2020)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most common analgesics used for pain relief. Adverse effects of NSAIDs range from gastrointestinal tract disturbances to increased risk of bleeding, renal injury,and myocardial infarction. In Malaysia, the research productivity of NSAIDs is not well explored. Objective: This study examined research productivity ofNSAIDs in Malaysia. Materials and Methods: This bibliometric study included all published research articles on NSAIDs from 1979 to 2018, which were conducted in Malaysia. The search databases such as Google Scholar, PubMed,ScienceDirect, and Scopus were used. Search terms included NSAIDs and specific drug names such as ibuprofen, celecoxib, and naproxen. Growth of publication, authorship pattern, citation analysis, journal index, type of studies, and geographical distribution of institutions publishing articles on NSAIDs were measured. Results: Overall, 111 articles were retrieved from 1979 to 2018. The annual productivity of articles throughout the study fluctuated in which the highest productivity was in 2018, 12.61% (n = 14). Majority of articles were multiple authored, 99.10% (n = 109), and University of Science Malaysia (USM) produced the highest number of articles (30 articles). Most of the articles were International Scientific Indexing-indexed, 52.25% (n = 58), and the main issue studied in most of the articles was the drug formulation of NSAIDs. Conclusion:The growth of NSAID research in Malaysia was slow, and the majority of research involved laboratory studies. Clinical studies evaluating the clinical outcomes of NSAIDs in patients, particularly using large healthcare databases are still lacking.